African Christian diaspora religion and/or spirituality: A concept analysis and reinterpretation - Counted, Victor (Critical Research on Religion, 2019)
The purpose of this article is to analyze how the concept of African Christian diaspora religion and/or spirituality, as a missionary-based model, is currently being used and defined within African transnational research and diaspora religion. I conducted a review using a citation search strategy to retrieve peer-reviewed articles that explore the extent to which the seminal paper of Steven Vertovec on “Diaspora Religion” has informed the conceptualization and analysis of the concept of African Christian diaspora religion and/or spirituality (ACDRS). The search generated empirical articles which met the inclusion criteria and were included for concept analysis. This concept analysis identified five emerging attributes of ACDRS as (a) a network of support, (b) a transnational dynamic, (c) a platform for civic engagement and activism, (d) the basis for developing place bonds and diaspora identity, and (e) as an experiential religion. These defining attributes position ACDRS as a multidimensional concept encompassing noninstitutionalized religious expressions and activities, albeit with limited empirical data. I also discussed some study limitations and conceptual issues related to the attributes, antecedents, consequences, and cases of ACDRS.
free
Keywords: Africa – Church history; Africa – Religion; African diaspora; Christianity and African religions; Human geography; Transnationalism; Vertovec; Steven